Ta’thīr Istikhdām Wasīlah al-Qiṣṣah al-Muqāṭaʿah fī Taḥsīn Mahārah al- Qirā’ah - Yosi Yunia Putri; Nur Hasnah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The problem in this study is the lack of activity in the reading Arabic texts among the students, wich leads to the decrease in the interest and enthusiasm for the learning the Arabic language. One of the teaching media that make it easier for students to fill the lessons so that they can achieve excellent results is the strip story. In addition to the interesting media, how to make it is also easy and does not require a lot of money. This media can be used as training in reading using illustrated text. The method used in this study is experimental method with True Experimental Design; Postest-Only Control Design, giving R (random) consisting of two design. The method of data collection, it is observation and tests and use of research analysis using the T-test rule. The writer founfd result of T computer is 3,098 and T table is 1,701, so the result it of the computational is greater than the tables T .The writer reached the conclusion that the use of the interrupted story method in the nine class in Alzamriyah islamic boarding School Simalanggang Payakumbuh in other words, the extent of influence on students reading skill is 20%. والمشكلة في هذه الدارسة قلة النشط في قراءة النصوص العربية لدى التلاميذ، مما يؤدي إلى انخفاض الإهتمام والحماس لتعلم اللغة العربية وقلة الرغبة لتعلم اللغة العربية. إحدى وسائل التعليمية التي تسهل على التلاميذ فعم الدروس حتى يتمكنوا من تحقيق نتائج ممتارة هي وسيلة القصة المقاطعة. بالإضافة إلى الوسيلة المثيرة للاهتمام، فإن كيفية جعلها سهلة أيضًا ولا تتطلب الكثير من المال. وهذه الوسيلة يمكن استخدامها كالتدريب على القراءة باستخدام النص المصور. نوع البحث هو البحث الكمي باستخدام الطريقة التجريبية. في هذا البحث استعملت الكاتبة تصميم بنوع True Eksperimental Design، Posttest-Only Control Design، تعطي Random ((R يتكون من التصميمين. وأما أسلوب جمع البيانات فهي الملاحظة والاختبارات. واستعمال تحليل البحث قاعدة اختبار